A randomised controlled trial of Hartmann's solution versus half normal saline in postoperative paediatric spinal instrumentation and craniotomy patients. Issue 6 (30th January 2012) - Coulthard, Mark G; Long, Debbie A; Ullman, Amanda J; Ware, Robert S
Abstract : Objective: To compare the difference in plasma sodium at 16–18 h following major surgery in children who were prescribed either Hartmann's and 5% dextrose or 0.45% saline and 5% dextrose. Design: A prospective, randomised, open label study. Setting: The paediatric intensive care unit (650 admissions per annum) in a tertiary children's hospital in Brisbane, Australia. Patients: The study group comprised 82 children undergoing spinal instrumentation, craniotomy for brain tumour resection, or cranial vault remodelling. Interventions: Patients received either Hartmann's and 5% dextrose at full maintenance rate or 0.45% saline and 5% dextrose at two-thirds maintenance rate. Main outcomes measures: Primary outcome measure: plasma sodium at 16–18 h postoperatively; secondary outcome measure: number of fluid boluses administered. Results: Mean postoperative plasma sodium levels of children receiving 0.45% saline and 5% dextrose were 1.4 mmol/l (95% CI 0.4 to 2.5) lower than those receiving Hartmann's and 5% dextrose (p=0.008). In the 0.45% saline group, seven patients (18%) became hyponatraemic (Na <135 mmol/l) at 16–18 h postoperatively; in the Hartmann's group no patient became hyponatraemic (p=0.01). No child in either fluid group became hypernatraemic. Conclusions: The postoperative fall in plasma sodium was smaller in children who received Hartmann's and 5% dextrose compared to those who received 0.45% saline and 5% dextrose. It is suggested that Hartmann's and 5% dextrose should be administered at full maintenance rate postoperatively to children who have undergone major surgery in preference to hypotonic fluids.